NOTE TAKING IN CONSECUTIVE TRANSLATION (KONFERENSIYA, 2026)
Note-taking in consecutive translation is a crucial skill that enables interpreters to organize information, identify key ideas, and convey the original message accurately. Notes are typically created using symbols, abbreviations, and personal conventions, which makes them understandable only to the interpreter. This article examines the fundamental principles of note-taking in consecutive translation and provides examples and exercises for developing this essential skill in practice